Штучний інтелект як ключ до безпеки електронної пошти - Шедін, Д. А.; Снігуров, А. В. (ХНУРЕ, 2023)
Email remains at the forefront of human-to-human communication. According to the statistics, the total daily number of letters is increasing. At the same time, threats spreading through this channel are also intensifying. Therefore, the purpose of the work is to improve the previously created system that is used to increase the level of electronic communication security by analyzing the sender’s domain and email headers. For this purpose, the implementation of artificial intelligence (is proposed. This work also defines the analysis of the capabilities of natural language processing models and their advantages over manual research, the technical stack, and the architecture of the future system.
Keywords: безпека електронної пошти; human-to-human communication